2018
DOI: 10.1177/1076029618764843
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Multicenter Trial Comparing Low-Dose Prednisolone Versus Observation for Prevention of Recurrences in Adult Immune Thrombocytopenia

Abstract: Adult immune thrombocytopenia (ITP) commonly relapses after stopping treatments. This may be preventable by low-dose steroids. In this multicenter study, adult patients with ITP who had been responding to corticosteroids were randomized with the 2 strata of newly diagnosed and relapsed ITP to prednisolone 7.5 mg/d or observation for 6 months. Relapses were defined by a platelet count below 30 × 10/L and/or clinical bleeding. There were 75 patients evaluable for the efficacy and 77 for safety. The recurrent ITP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The IC 50 of rilzabrutinib for inhibition of human B cell proliferation was 5 6 2.4 nM. Rilzabrutinib did not block ADCC in combination with anti-CD20 Abs, indicating potential for combination therapies (26).…”
Section: Blockade Of B Cell Activation Igm and Igg Ab Production Wimentioning
confidence: 96%
“…The IC 50 of rilzabrutinib for inhibition of human B cell proliferation was 5 6 2.4 nM. Rilzabrutinib did not block ADCC in combination with anti-CD20 Abs, indicating potential for combination therapies (26).…”
Section: Blockade Of B Cell Activation Igm and Igg Ab Production Wimentioning
confidence: 96%
“… 8 Long-term corticosteroids should be avoided in most cases because they are poorly effective in maintaining remission at a low dose and do not affect the ITP natural history while generating side effects. 58 , 59 Prednisone 1 mg/kg for 3 weeks or dexamethasone 40 mg/day for 4 days (repeated up to three times if necessary) can be used. A number of controlled studies have suggested a faster and greater platelet response with dexamethasone over prednisolone, but the rate of long-term response was similar in both groups.…”
Section: Itp Treatments: What Tolerance and What Efficacy In Older Pa...mentioning
confidence: 99%
“…Most patients respond to corticosteroids with a rise in platelet count, but improvements are usually transient and the majority of patients will relapse [5,26]. Although prolonged corticosteroid therapy may maintain a hemostatic platelet count in responding patients, it does not enhance the rate of remission [5,33] and long-term use is linked with a number of side effects that can be…”
Section: Corticosteroidsmentioning
confidence: 99%